Effects of Single and Hybrid Steel Fiber Lengths and Fiber Contents on the Mechanical Properties of High-Strength Fiber-Reinforced Concrete - Kyoung-Chul Kim; In-Hwan Yang; Changbin Joh (Advances in Civil Engineering)
This paper describes an experimental study on the mechanical properties of high-strength fiber-reinforced concrete (HSFRC). The experimental parameters included the content and length of the steel fiber as well as the use of either a single-type fiber or hybrid steel fibers. The steel fiber contents were 1.0, 1.5, and 2.0% based on the volume of HSFRC, and the steel fiber lengths were 13, 16.5, and 19.5 mm. In addition, hybrid steel fibers incorporating steel fibers of different lengths were used. Compression tests and crack mouth opening displacement tests were performed for each HSFRC mixture with different experimental parameters. The mechanical properties of the HSFRC, such as compressive strength, elastic modulus, and tensile strength, increased with the steel fiber content. The mechanical property results of the HSFRC mixture using a single fiber length of 13 mm were greater than the results of the other mixtures. The compressive strength, elastic modulus, and tensile strength of the HSFRC mixture with hybrid steel fibers were similar to those of the mixtures with a single length of steel fiber. Additionally, based on the test results of the material properties, equations for predicting the elastic modulus and tensile strength of the HSFRC were suggested; the predictions using the proposed formula closely agreed with the experimental results.